Using Mechanical Bonds to Probe Molecular Interactions - Andersen, Nathan (2022)
Mechanically interlocked molecules (MIMs), the class of compounds involving a mechanical bond between two or more molecules, have garnered much attention within the field of supramolecular chemistry, particularly for their unique structures and interactions exhibited. Pillar[n]arenes (PnA) – pillar shaped, rigid macrocycles (MCs) of n repeating dihydroxyl benzene monomers, with an electron rich cavity and myriad iterations through functionalisation of the 2n-hydroxyl groups – are an exciting class of MC investigated herein. Common alkoxy derivatives are reported, such as per-methoxy (MeP5A) which is herein synthesised, via co-condensation yielding a mono-substituted analogue (MSMeP5A) alongside MeP5A, and its MIM products are investigated. Homologues of pillararenes (P6A, P7A, P8A, etc.) are shown to be accessible via alternative solvent templating. The synthesis of MeP6A, rarely observed in the literature, was investigated, giving low yields, due to poor homologue selectivity through kinetically controlled conditions. The guest component of MIMs within the focus of this study, bears ‘stations’ of favourable interactions towards the MC; of particular note, are imidazolium motif interactions with the pillarene cavity, with association constant (Ka) values of up to 2 x 104 M 1 observed in the literature. [2]Rotaxanes comprised of bis(imidazolium)octane and bis(imidazolium)dodecane axles, stoppered by mesityl functionalised caps, interlocked with MeP5A were synthesised in good yields. As analogous structures of MeP6A with imidazolium stations are not thus far reported, the synthesis of these structures was also investigated. Alternative stoppers with larger steric bulk than mesitylene, such as anthracene, were employed to test this, although rotaxane product formation also wasn’t observed. In previous work, it was shown that per-cyclohexylmethoxyP6A (CHMP6A) also could not form [2]rotaxanes with bis(imidazole) axles, even though inclusion complexes of CHMP5A, with smaller cavity sizes and equal alkoxy motif steric bulk, are reported in the literature. As such, we reason that the larger cavity of P6A MCs limits favourable interactions with imidazole groups and a guest size with better shape complementarity should assist in the construction of host-guest complexes of P6A. Rylene diimides (RDI) are widely investigated chromophores, owing to their unique photophysical properties and chemically robust nature. Research attempting to isolate dimers of these chromophores typically uses covalent means (i.e. cyclophanes), but a mechanically bonded approach takes advantage of more flexible interactions. Examples of rotaxane based dimeric systems are rare, therefore to broaden the scope of available structures, a toolbox of mechanically interlocked rylene imide based rotaxanes was synthesised, characterised, and their interactions probed through NMR shielding effects analysis. The toolbox includes approaches to both symmetric and asymmetric rotaxane synthesis and includes a MIM with three π-stacked layers. The asymmetric structures were dubbed ‘Tweezer’ [2]rotaxanes, due to the structural resemblance and motion possible in the structure. It was observed that the (MS)MeP5A MCs were localised about the single imidazolium station of the axle. Where monofunctionalised (MSMeP5A) MCs were used, which carried pendent rylene motifs, this localisation caused the rylene motifs to be held together at specific lateral distances, depending upon the ratio of alkyl chain length between the axle and MC substituent. An optimal ratio of 2:1, in favour of axle chain length, was shown, where a small increase to 2.5:1 results in half the observed shielding effects. The effect of rylene interactions was discernible through comparison to both [2]rotaxane analogues with a MeP5A MC and, therefore, no intramolecular rylene stacking, and also with the directional threading isomers of the Tweezer rotaxanes, whereby the ‘arm’ of the MSMeP5A points the opposite direction, such that the rylenes are oriented in an anti-parallel fashion, opposite to the parallel conformation which exhibits the shielding effects. Similar directional threading isomers were observed in the triply stacked [3]rotaxane, where a central perylene diimide (PDI) chromophore was flanked by octyl-imidazolium groups, stoppered with a mesityl motif, interlocked symmetrically with two MSMeP5A MCs bearing pendent naphthalimide (NI) motifs. In this way, the two MCs could independently be oriented in the parallel or anti-parallel conformations, resulting in three directional threading isomers, which could be evidenced by the shielding effects of the MC upon the axle in NMR experiments. Lastly, singlet fission (SF) is a spin-allowed electronic process whereby an excited singlet state, of a suitable chromophore, may share its excitation with a neighbouring molecule, resulting in two harvestable, lower energy, triplet states, which may be exploited to improve the maximum possible efficiency of photovoltaic (PV) devices. Despite some progress, a deep understanding of the mechanism of SF remains to be elucidated. It is proposed that molecular handcuffs, a particular type of MIM, may be used to probe chromophore interactions in a SF process. Progress has been made towards the design and synthesis of a mechanically bonded dimer of pentacene, a primary SF candidate chromophore, for examination in the solid and solution phases. Different approaches to the incorporation of pentacene into a molecular handcuff are examined, to address issues with stability and solubility of the synthesis intermediates. Handcuff structures of terylene diimide (TDI) are also considered as alternative SF candidates taking advantage of synthetic protocols developed in previous chapters.